A PROSPECTIVE STUDY OF PRESCRIBING PATTERN OF INSULIN IN PATIENTS WITH TYPE 2 DIABETES MELLITUS ADMITTED IN MEDICINE WARDS - SHRUTI VIHANG BRAHMBHATT; RUSHI DEWANG DAVE; HITANSHI BHARATBHAI PATEL (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: The prevalence of Diabetes Mellitus is increasing exponentially. The present research is mainly focusing on study the prescription pattern and rationality of insulin prescribed in patients with type 2 Diabetes. It also reviews acceptance to the insulin therapy in type 2 diabetes patients. This research focuses on events of adverse drug reaction and also reviews adherence with the latest American Diabetic Association (ADA) guidelines. Methodology: A study was conducted in 50 diabetic patients admitted in medicine wards. Patients were included in the study only after obtaining written informed consent form. Fasting blood sugar and post prandial blood sugar level was noted on the day of admission and on the day of discharge. Result: Out of 50 patients, human actrapid (HAI) according to sliding scale was the most commonly prescribed (66%) insulin followed by HAI + Lantus (30%) and mixtard (4%). In addition to insulin, 23 patients (46%) were given oral hypoglycemic agents out of which majority (60.8%) were on combination therapy with metformin, sulfonylureas and DPP-4 inhibitors. Total 28% of patients had shown adherence and acceptability with the therapy. About 86% of prescriptions in present study were adherent to guidelines of American Diabetes association. Conclusion: Study shows that HAI therapy according to sliding scale remains the first choice of treatment in type 2 diabetes patients in rural area where data is insufficient. Poor adherence was observed among the patients towards insulin therapy which may be due to lack of awareness.